Answer:
![x=6-3√(10)\text{ or }x=6+3√(10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/w8k1g8e3rxg0a1dwmeqc8r64f23t9f9vfr.png)
Explanation:
We have been given an equation
. We are asked to solve for x in our given equation.
We can see that left side of our given equation is a perfect square.
![(x-6)^2=90](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ss96oyhzhzcz4ej762uuq03y893zfeyd8n.png)
We will take square root of both sides of our given equation to solve for x.
![√((x-6)^2)=\pm√(90)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mn3xwgssuqzn9iqs0npurcxphob6p2nboj.png)
Using radical rule
, we will get:
![x-6=\pm√(90)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ylwd93bzm6nbzkk59s9wiqqir9yjq8q7qo.png)
![x-6=\pm√(9\cdot 10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/dhjhl3xeev2fwmy3nm2h1jz3v5ktnxh9dp.png)
![x-6=\pm√(3^2\cdot 10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/736mzxh1xd02zf96lgh1wlxine3f1rup1f.png)
![x-6=\pm√(3^2)\cdot √(10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ekl0zww63dzs1hm2iithy1od5696dcpa5o.png)
Using radical rule
, we will get:
![x-6=\pm3√(10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/64ag0cmvgqb2gt4g0u1p5s9h96wg5l9yo9.png)
Now, we will add 6 on both sides of our given equation as:
![x-6+6=\pm 3√(10)+6](https://img.qammunity.org/2019/formulas/mathematics/middle-school/oiybs4dq3m2k11y90nszaqz3ykyshi9r2f.png)
![x=\pm 3√(10)+6](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qz2cznh6f034lsf6h3pil66na1eylf4yjl.png)
![x=-3√(10)+6\text{ or }x=3√(10)+6](https://img.qammunity.org/2019/formulas/mathematics/middle-school/97kk6gybggpaqgutt0vd9sxubuok6d4yog.png)
![x=6-3√(10)\text{ or }x=6+3√(10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/w8k1g8e3rxg0a1dwmeqc8r64f23t9f9vfr.png)
Therefore, the solution for our given equation would be
.